Processing image system for user head movement recognition - Ungurean, Ciprian Ovidiu (Оптико-електронні інформаційно-енергетичні технології, 2009)
The aim of the paper is to describe a system for the head gesture recognition developed in the frame of INTEROB project which is financed by the research grant 131-CEEX-II03/02.10.2006. The goal of this project consists in developing an interaction based on gestures with information on robotic systems. In the paper we discussed a method for controlling the mouse pointer movements on the screen by recognizing the operator head movements captured by a video camera.